2015
DOI: 10.1088/0953-8984/27/43/435007
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-assisted magnetotransport in two-dimensional electron gas systems: appearance of zero resistance states

Abstract: Zero-resistance states (ZRS) are normally associated with superconducting and quantum Hall phases. Experimental detection of ZRS in two-dimensional electron gas (2DEG) systems irridiated by microwave(MW) radiation in a magnetic field has been quite a surprise. We develop a semiclassical transport formalism to explain the phenomena. We find a sequence of Zero-Resistance States (ZRS) inherited from the suppression of Shubnikov-de Haas (SdH) oscillations under the influence of high-frequency and large amplitude m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Numerical simulations have been performed [6,69,70] to propose appropriate setups for the observation of ZB experimentally. Later on, it was found that such trembling motion of electron can also appear in crystalline solid materials with their band structure described by a two band model [8,54,57,58,60,61,71,72]. The notion of zitterbewegung plays very important role in understanding the dynamical features investigated in this paper.…”
Section: Optical Radiation Effects On Cyclotron Motionmentioning
confidence: 78%
See 2 more Smart Citations
“…Numerical simulations have been performed [6,69,70] to propose appropriate setups for the observation of ZB experimentally. Later on, it was found that such trembling motion of electron can also appear in crystalline solid materials with their band structure described by a two band model [8,54,57,58,60,61,71,72]. The notion of zitterbewegung plays very important role in understanding the dynamical features investigated in this paper.…”
Section: Optical Radiation Effects On Cyclotron Motionmentioning
confidence: 78%
“…In recent years, there has been much interest in simulations of relativistic quantum effects using different physical set-ups [5,6], in which parameter tunability allows access of different physical regimes. On the other hand, radiation-matter interaction has significant effects on the electron dynamics [7][8][9][10][11][12][13][14]. For instance, when a high mobility two dimensional electron gas (2DEG) is irradiated by microwave radiation in a weak magnetic field, the longitudinal magneto-resistance exhibits giant oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of experiments conducted in the last decade, it was discovered that the kinetic properties of a quantum well subjected to deformation, temperature, ultra-high frequency electromag-netic field, deformation and light in the applied magnetic field provide even richer information for the theory of quantum physics. In particular, in the works [4,5], in the quantum well GaAs, the semiclassical theory of magnetoresistance oscillation during irradiation with microwaves is analyzed. In a quantizing magnetic field, the specific magnetoresistance of the system demonstrates Shubnikov-de Haase oscillations at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Such oscillations exhibit a non-linear variation in the oscillatory amplitude with radiation power, 15,25,36 sensitivity in the oscillatory amplitude to the orientation of the linearly polarized radiation with respect to the device, 19,[25][26][27][28]35 etc. Many theoretical explanations have been proposed to help understand associated phenomena, [36][37][38][39][40][41][42][43][45][46][47][48][49][50][51][53][54][55][56][57][58][59][60][61][62][63][64] including, for example, mechanisms based on (a) the scattering of electrons by phonons and impurities between Landau levels, 37,40,42,43 (b) the periodic motion of electron orbit centers under photoexcitation, 38,48 , (c) the inelastic model, 45 and (d) the re-collision of cyclotron electrons from scattering centers. 63 Previous work 6,…”
Section: Introductionmentioning
confidence: 99%